2010
DOI: 10.1038/aps.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triptolide on RIZ1 expression, proliferation, and apoptosis in multiple myeloma U266 cells

Abstract: Aim: To investigate the effects of triptolide on proliferation and apoptosis as well as on the expression of RIZ1 in the human multiple myeloma cell line U266 in vitro. Methods: The effect of triptolide on the growth of U266 cells was studied by MTT assay. Apoptosis was detected by Hoechst 33258 staining and Annexin V/PI double-labeled flow cytometry, and caspase-3 mRNA was measured by RT-PCR. Western blotting, flow cytometry and RT-PCR were used to assess the expression of RIZ1, and the location and expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The rates of inhibition by 50, 100, and 150 nmol/L triptolide were 34.7%, 29.4%, and 39.6%, respectively; (P<0.05 vs untreated control) ( Figure 7B). We also found that the expression of trimethylated H3K9 decreased in RPMI8226 cells, and monomethylated H3K9 was elevated in U266 cells in a dose-dependent manner following treatment with increasing concentrations of triptolide [15,18] .…”
Section: Triptolide Induced Apoptosis In Rpmi8226 Cells and Pbmcsmentioning
confidence: 54%
See 1 more Smart Citation
“…The rates of inhibition by 50, 100, and 150 nmol/L triptolide were 34.7%, 29.4%, and 39.6%, respectively; (P<0.05 vs untreated control) ( Figure 7B). We also found that the expression of trimethylated H3K9 decreased in RPMI8226 cells, and monomethylated H3K9 was elevated in U266 cells in a dose-dependent manner following treatment with increasing concentrations of triptolide [15,18] .…”
Section: Triptolide Induced Apoptosis In Rpmi8226 Cells and Pbmcsmentioning
confidence: 54%
“…H3K36me2/me3 are enriched mostly in the transcribed region of active genes and are associated with the later stages of transcription in actively transcribed regions [18] . However, a direct association between H3K36me2 and proapoptotic genes has not been proven; further investigation will be required to clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were resuspended in 200 μL Annexin-binding buffer containing 10 μL Annexin V-FITC and 5 μL PI. After 30 min of incubation in the dark, 300 μL phosphate buffer saline (PBS) were added into cells, and the apoptotic cells were distinguished under a flow cytometry (Beckman Coulter, CA, USA) immediately (Zhao et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the search for novel drugs for the treatment of PD is an important endeavor. Triptolide is one of the major active components of the Chinese herb Tripterygium wilfordii Hook F. It is well known that triptolide has anti-inflammatory, immunosuppressive, contraceptive and antitumor properties [3][4][5] . Some studies indicate that PD is a chronic neuroinflammatory process, and triptolide has been found to possess antiparkinsonian effects [6] .…”
Section: Introductionmentioning
confidence: 99%